IL-12 inhibits the TGF-β-dependent T cell developmental programs and skews the TGF-β-induced differentiation into a Th1-like direction - Prochazkova, Jana; Pokorna, Katerina; Holan, Vladimir (Immunobiology, 2012)
The development and differentiation of T helper (Th) cell subsets is a highly plastic process which is strictly regulated by cytokines. Here we show that the transforming growth factor β (TGF-β)-dependent differentiation programs are negatively regulated by interleukin-12 (IL-12). The development of TGF-β-induced regulatory T cells (iTregs) or TGF-β/IL-6 activated Th17 cells from purified mouse CD4(+)CD25(-) T cells, stimulated with monoclonal antibody anti-CD3, was abrogated in the presence of IL-12 and a different developmental program was established. On the molecular level, IL-12 inhibited the expression of the lineage specific transcription factors Foxp3 and RORγt in developing Tregs and Th17 cells, respectively. Moreover, IL-12 was able to alter the development of iTregs and Th17 cells even when added to the differentiating cells after 48h of the culture. The cells activated in the presence of TGF-β and IL-12 had an increased expression of the Th1 transcription factor T-bet, produced Th1 cytokines interferon γ and IL-2 and expressed IL-18 receptor and C-C chemokine receptor type 5 which are the phenotypic markers characteristic for Th1 cells. Furthermore, the cells activated in the presence of both TGF-β and IL-12, and not of TGF-β only, stimulated macrophages to produce nitric oxide. Altogether, these results indicate that IL-12 is a superior cytokine that has the ability to skew the already ongoing TGF-β-dependent iTreg or Th17 developmental program into Th1-like direction.
Keywords: Nitric Oxide; exprese genu; Gene Expression; Interleukin-12; Male; Nuclear Receptor Subfamily 1, Group F, Member 3; forkhead transkripční faktory; Interferon-gamma; Transforming Growth Factor beta; Interleukin-2; Th1 buňky; regulační T-lymfocyty; signální transdukce; buněčná diferenciace; Interleukin-6; Receptors, Interleukin-18; myši inbrední BALB C; interferon gama; Forkhead Transcription Factors; oxid dusnatý; mužské pohlaví; Th17 Cells; receptory interleukinu-18; Th1 Cells; Signal Transduction; Mice, Inbred BALB C; transformující růstový faktor beta; Receptors, CCR5; jaderné receptory - podrodina 1, skupina F, člen 3; T-Lymphocytes, Regulatory; Animals; interleukin-2; ženské pohlaví; interleukin-6; zvířata; makrofágy; myši; receptory CCR5; Mice; Female; Macrophages; interleukin-12; buňky Th17; Cell Differentiation